Reproducibility of Her2/neu scoring in gastric cancer and assessment of the 10% cut‐off rule. (16th December 2014) - Behrens, Hans‐Michael; Warneke, Viktoria S.; Böger, Christine; Garbrecht, Nele; Jüttner, Eva; Klapper, Wolfram; Mathiak, Micaela; Oschlies, Ilske; Rudolph, Ursula; Stuhlmann‐Laeisz, Christiane; Trick, David; Röcken, Christoph; et al.
Abstract The application of Trastuzumab on gastric cancer patients is based on Her2/neu immunostaining. The testing method relies on visual estimation of both membranous staining intensity, and positive tumor ratio with respect to a 10% cutoff. We evaluated the effect of inter‐ and intraobserver variations of both factors on therapeutic decision, especially if the positive tumor ratio hovers around the 10% cutoff. Ten pathologists scored 12 Her2/neu immunohistologically stained whole sections of gastric cancer. Applying the common rules for Her2/neu testing for gastric cancer, they separately noted the strongest identifiable staining intensity and the corresponding positive tumor ratio. Scoring was done repeatedly using the microscope, plain virtual microscopy, and virtual microscopy with a manual outline drawing function. Agreements on the strongest identified staining intensities were moderate. Overall concordance correlation coefficients of positive tumor ratios ranged from 0.55 to 0.81. Reproducibility was not improved by virtual microscopy. Pathologists have a good ability to estimate ratios of clearly demarcated areas, but gradients in staining intensities hinder reproducible visual demarcation of positive tumor areas. When hovering around the 10% positive tumor ratio cutoff there is a risk of misinterpretation of the staining results. This could lead to a denial of Trastuzumab therapy. Assessment of Her2/neu expression should be carried out by experienced pathologists because they can more reproducibly rate membranous staining intensities. The low reproducibility of positive tumor ratio is inherent in the testing method and cannot be improved by virtual microscopy. Therefore, we propose to reconsider the 10% cut‐off limit.